1. Multiply and simplify.

a) (b + 2)(b + 2)

b) (x + 3)(x – 3)

Answer:

1. Simplify.

a) (3xy^{3})(2x^{3}y)

b) 2y(2y + 3y^{2}) – y^{2}(3 – y)

Good Luck

can you type it.....it's hard to read ur hand writng

all right, a few minutes

(a) (b+2)(b+2)

= b(b+2) + 2(b+2)

=b^{2} + 4b + 4 (answer)

(b) (x+3)(x-3)

= x(x-3) + 3(x-3)

= x^{2} – 3x + 3x -9

= x^{2} – 9 (answer)

(a) (3xy^{3})(2x^{3}y)

= (3*2)(x.x^{3})(y^{3}.y)

= 6x^{4}y^{4 }

^{ }

(b) 2y(2y + 3y^{2}) – y^{2}(3-y)

= 4y^{2} + 6y^{3} – 3y^{2} + y^{3}

= 4y^{2} – 3y^{2} + 6y^{3} + y^{3}

= y^{2} + 7y^{3}

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up